2017
DOI: 10.1177/0957650917724598
|View full text |Cite
|
Sign up to set email alerts
|

Effect of casing aspiration on the tip leakage flow in the axial flow compressor cascade

Abstract: Tip leakage flow is usually responsible for the deterioration of compressor performance and stability. The current paper conducts numerical simulations on the impact of casing aspiration on the axial compressor cascade performance. Three aspiration schemes with different chordwise coverage are studied and analyzed. It is found that the cascade performance can be effectively improved by the appropriate casing aspiration, and the optimum aspiration scheme should cover the area including the onset point of tip le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…The central difference method and the fourth-order Runge–Kutta iterative method are used to discretize the space and time terms of the control equations. According to the previous research experience of our research group [ 18 , 19 ], the one-equation S-A turbulence model has the better convergence and stability than the other two equation models, and it is also found that this turbulence model can accurately predict the flow in the cascade, compared with the experimental results. Therefore, the S-A turbulence model is selected to simulate the internal turbulence in current research.…”
Section: Investigated Compressor Cascade and Numerical Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…The central difference method and the fourth-order Runge–Kutta iterative method are used to discretize the space and time terms of the control equations. According to the previous research experience of our research group [ 18 , 19 ], the one-equation S-A turbulence model has the better convergence and stability than the other two equation models, and it is also found that this turbulence model can accurately predict the flow in the cascade, compared with the experimental results. Therefore, the S-A turbulence model is selected to simulate the internal turbulence in current research.…”
Section: Investigated Compressor Cascade and Numerical Methodsmentioning
confidence: 90%
“…In recent years, this technique has also been used to control the TLF in the clearance, and it can be divided into two categories according to different aspiration positions: one is the blade tip suction (BTS) and the other is the endwall suction (ES). Mao et al [ 18 , 19 ] studied the influence of the axial position of the suction slot on the TLF of the compressor cascade controlled by the BTS and ES respectively. The results showed that both aspiration schemes could effectively reduce the TLF intensity and flow loss of the compressor cascade.…”
Section: Introductionmentioning
confidence: 99%
“…The calculation results are dependent on the chosen software, turbulence models, and solver settings. The CFD code used in this study was the Numeca Fine/Turbo solver, which has been widely used in many academic institutes and industry companies [ 37 , 38 ]. The steady Reynolds-averaged Navier–Stokes equation was carried out in the present paper.…”
Section: Geometry and Flow Analysis Of The Baseline Cascadementioning
confidence: 99%
“…The results showed that the flow control effect was the best when the suction slot was positioned directly above the blade tip, and the flow control effect increased with the increase of suction flow rate (SFR, defined as the ratio of the suction mass flow rate to the inlet mass flow rate.). Some scholars have also studied the flow control of the TLF by slotting or grooving suction on the rotor casing and had a better understanding of the mechanism of BLS to suppress the TLF and TLV (Gümmer et al 2008;Lu et al 2017a;Perry et al 2017;Mao et al 2017Mao et al , 2018b.…”
Section: Introductionmentioning
confidence: 99%